ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PEGAWAI PADA PT BETAMI - Khairi, Mujibur (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2022)
This research is used to determine whether leadership style and work environment affect employee job satisfaction. The research implementation is located at PT Betami with a sample of 31 respondents. This study uses a Likert scale. Data analysis used multiple linear regression. The results of the study concluded that the results of the t test of leadership style and work environment had no significant positive effect on employee job satisfaction, but through the F test, both had a significant positive effect.